Fabrication of carbon layer coated FE-nanoparticles using an electron beam irradiation. (January 2016) - Kim, Hyun Bin; Jeun, Joon Pyo; Kang, Phil Hyun; Oh, Seung-Hwan
Abstract: A novel synthesis of carbon encapsulated Fe nanoparticles was developed in this study. Fe chloride (III) and polyacrylonitrile (PAN) were used as precursors. The crosslinking of PAN molecules and the nucleation of Fe nanoparticles were controlled by the electron beam irradiation dose. Stabilization and carbonization processes were carried out using a vacuum furnace at 275 °C and 1000 °C, respectively. Micro structures were evaluated by X-ray diffraction (XRD) and transmission electron microscopy (TEM). Fe nanoparticles were formed with diameters of 100 nm, and the Fe nanoparticles were encapsulated by carbon layers. As the electron beam irradiation dose increased, it was observed that the particle sizes decreased. Highlights: Carbon layer coated Fe-nanoparticles were successfully synthesized. The size of iron nanoparticles is controlled by electron beam irradiation dose. The encapsulation is confirmed between the carbon layer and iron nanoparticle.